2019
DOI: 10.3390/ijerph16122177
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Literature Review of the Take-Home Route of Pesticide Exposure via Biomonitoring and Environmental Monitoring

Abstract: Background: Exposure to pesticides via take-home can be an important pathway for farmworkers' families. Objective: The aim of this review was to summarize and analyze the literature published during the last decade of exposure to pesticides via take-home pathway in farmworkers' families. Methods: We conducted a systematic review to identify peer-reviewed articles of interest; only articles related to take-home pathway that included some sort of pesticide monitoring were considered for inclusion. Systematic rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 54 publications
1
27
0
2
Order By: Relevance
“…Children are exposed to pesticides through multiple pathways, which can include: having a mother exposed to pesticides while pregnant, living or studying near areas with pesticide use, attending agricultural areas, having parents working in agriculture, having residential exposure through take-home exposure, and eating and drinking contaminated food and water, among others [10,37]. A hospital-based multisite study in Sri Lanka observed that most children poisoned with pesticides had at least one parent engaged in farming activities (~58%), and were exposed at cultivation sites (~51%) [38].…”
Section: Resultsmentioning
confidence: 99%
“…Children are exposed to pesticides through multiple pathways, which can include: having a mother exposed to pesticides while pregnant, living or studying near areas with pesticide use, attending agricultural areas, having parents working in agriculture, having residential exposure through take-home exposure, and eating and drinking contaminated food and water, among others [10,37]. A hospital-based multisite study in Sri Lanka observed that most children poisoned with pesticides had at least one parent engaged in farming activities (~58%), and were exposed at cultivation sites (~51%) [38].…”
Section: Resultsmentioning
confidence: 99%
“…Besides, some other symptoms are revealed during moderate poisoning status including nausea, vomiting, headache, lacrimation, excessive salivation, respiratory depression, seizures, loss of consciousness, reduced visual ability, allergy, abdominal cramps, and rapid pulse. In severe poisoning exhibit inability to breathe, extra phlegm or mucous in the air routes, burn of the skin, increase the rate of breathing, pulmonary fibrosis, myocarditis and necrosis, pancytopenia, and adrenal hemorrhage, loss of reflexes, extreme weakness, and even death [35,2,10,36,37].…”
Section: Pesticide Effects On Humansmentioning
confidence: 99%
“…Children are exposed to pesticide through multiple pathways, that can include: having a mother exposed to pesticides while pregnant, living or studying near areas with pesticide use, attending agricultural areas, having parents working in agriculture, having residential exposure by take-home exposure, eating and drinking contaminated food and water, among others López-Gálvez et al, 2019). A hospital-based multisite study in Sri Lanka observed that most children poisoned with pesticides had at least one parent engaged in farming activities (~58%), and were exposed at cultivation sites (~51%) (Dayasiri et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Diversos fatores podem aumentar a exposição das crianças aos pesticidas, como por exemplo, a ocupação dos pais ou responsáveis, aplicação de pesticidas domésticos, proximidade residencial ou das escolas de áreas de aplicação e armazenagem de pesticidas, número de trabalhadores rurais expostos aos pesticidas vivendo no mesmo domicílio, tipo de cultivo, entre outros López-Gálvez et al, 2019;Muñoz-Quezada et al, 2012).…”
Section: Efeitos à Saúde Da Exposição Ambiental Aos Pesticidasunclassified
See 1 more Smart Citation